#MeToo and modernism - Field, Robin E., 1976-; Jordan, Jerrica ([Clemson, SC] : Clemson University Press, 2022)
"#MeToo and Modernism opens new critical conversations about modernism and power, privilege, and patriarchy to uncover a united literary movement against sexual violence. This volume showcases how authors, whether purposely or not, challenge patriarchal viewpoints regarding sexuality, gender, and race and allowed readers different methods of interpretation for trauma narratives"--
Introduction: #MeToo and modernism / Robin E. Field and Jerrica Jordan -- Questioning modern misogyny. "I'd have my life unbe": undoing experience in Tess of the d'Urbervilles / Bailey Shaw -- Muses and misogyny in decadent modernism / Angie Blumberg -- Defiant martyrs, repentant sinners, and pioneer players: translating and transforming the works of Hrotsvit of Gandersheim / Ben Lee Taylor -- Ford's creepy candor / Beci Carver -- #MeToo, modernism, and trauma. Locating women's shared trauma and precursors to the #MeToo movement in Virginia Woolf's The voyage out and Moments of being / Ellen Campbell -- The phonograph as witness: new media's #MeToo evolution / Zan Cammack -- Street harassment in Wells, Joyce, and Woolf / Candis E. Bond -- "full yell of full woman, delight, joy, indignation": women out-spoken in Joyce's Ulysses / Michael Levenson -- Aftermath: outrage and its reactions. Modernist memoir and the social structures of sexual violence / Emma Heaney -- What happened in the Cane? A rereading of Jean Toomer's "Fern" / Samantha Wallace -- Histories of rape resistance: revolution in Ann Petry's The street / Jerrica Jordan -- Why all rape is interracial: Wide Sargasso Sea and the possibility of feminist solidarity / Carine Mardorossian -- #MeToo modernist pedagogy. Rescuing women from historical amnesia: how three twenty-first-century TV series address #MeToo and foreground the role of women in the twenty-first century / Daniel R. Schwarz -- #MeToo vs. modernism in the classroom / Cara L. Lewis -- "Equally, if you stop to laugh": teaching the humor of A room of one's own in the #MeToo classroom / Lauryl Tucker.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on March 13, 2023).
JSTOR
Keywords: Sex crimes in literature; Literature -- History and criticism; Misogyny in literature; Feminism in literature; Modernism (Literature); MeToo movement; Literature -- Study and teaching; Violence sexuelle dans la littérature.; Littérature -- Histoire et critique; Misogynie dans la littérature.; Féminisme dans la littérature.; Modernisme (Littérature); Mouvement #MoiAussi.; Littérature -- Étude et enseignement; Feminism in literature; Literature; Literature -- Study and teaching; MeToo movement; Misogyny in literature; Modernism (Literature); Sex crimes in literature; Criticism, interpretation, etc; Essays; Literary criticism; Literary criticism; Essays; Critiques littéraires.